Pursued economy : understanding and overcoming the challenging new realities for advanced economies - Koo, Richard (John Wiley & Sons Ltd, 2022)
"Human progress is said to have started when civilizations sprang up in China, Egypt, and Mesopotamia over 5,000 years ago. The Renaissance, which began in Europe in the 13th century, accelerated the search for both a deeper understanding of the physical world and better forms of government. But for centuries, that progress benefited only the fortunate few with enough to eat and the leisure to ponder worldly affairs. Life for the masses was little better in the 18th century than it was in the 13th century when the Renaissance began. Thomas Piketty noted in his book Capital in the Twenty-First Century that economic growth was basically at a standstill during this period, averaging only 0.1 percent per year"--